Sarcopenia index based on serum creatinine and cystatin C is associated with all-cause mortality in patients aged 50 and over with hip fracture - Longqing Yu; Fupeng Liu; Qiuping Zhang; Wenhua Yan; Mei Zhang (Experimental Gerontology)
Background: Sarcopenia index (SI), calculated as serum creatinine/cystatin C × 100, has emerged as a potential marker for muscle loss and adverse outcomes. However, its prognostic value in hip fracture patients remains unclear. This study aimed to investigate the association between SI and all-cause mortality in patients aged 50 and over with hip fracture. Methods: This study included patients aged 50 and over with low-energy hip fractures and followed them for at least two years to track the incidence of death. Collect baseline demographic, clinical and biochemical data. Kaplan-Meier and log-rank analyses were performed to compare the mortality between different SI levels. Univariate and multivariate cox regression models were used to evaluate the relationship between SI and all-cause mortality in patients aged 50 and over with hip fracture. Subgroup analysis was carried out to evaluate the influence of potential regulators, and cubic spline curves were limited to check the potential nonlinear relationship between SI and all-cause mortality. Results: A total of 637 patients were enrolled in the study, 62 deaths occurred during follow-up. Non-survivors were significantly older (80.02 ± 9.24 vs 71.05 ± 10.75 years, P < 0.001) and had lower SI values (54.06 ± 11.17 vs 61.51 ± 14.51, P < 0.001) compared to survivors. Kaplan-Meier analysis showed significantly better survival in the high SI group (P = 0.0034). In multivariate analysis, SI remained independently associated with mortality after adjusting for comprehensive covariates (HR = 0.98, 95 % CI: 0.95–0.99, P = 0.018). Restricted cubic spline analysis revealed a nearly linear relationship between SI and the risk of death in patients with hip fractures. In subgroup analysis except in diabetes and BMI ≥ 24, SI was negatively correlated with the second hip fracture. Conclusions: Lower SI values are independently associated with increased all-cause mortality in patients aged 50 and over with hip fracture. SI might serve as a valuable prognostic marker for risk stratification in this population, potentially helping identify high-risk patients who may benefit from more intensive monitoring and intervention.